The Involvement of Heat Shock Proteins in the Establishment of Tomato Yellow Leaf Curl Virus Infection - Gorovits, Rena; Czosnek, Henryk (Frontiers in Plant Science, 2017)
TTomato yellow leaf curl virus (TYLCV), a begomovirus, induces protein aggregation in infected tomatoes and in its whitefly vector Bemisia tabaci. The interactions between TYLCV and HSP70 and HSP90 in plants and vectors are necessity for virus infection to proceed. In infected host cells, HSP70 and HSP90 are redistributed from a soluble to an aggregated state. These aggregates contain, together with viral DNA/proteins and virions, HSPs and components of the protein quality control system such as ubiquitin, 26S proteasome subunits, and the autophagy protein ATG8. TYLCV CP can form complexes with HSPs in tomato and whitefly. Even though HSP70 and HSP90 are similarly recruited in virus-induced aggregates, their roles in the viral cell cycle in the plant host are different. HSP70, but not HSP90, is important for the viral CP shuttling from cytoplasm into nuclei. Viral amounts decrease when HSP70 is inhibited, but increase when HSP90 is downregulated. In the whitefly vector, HSP70 impairs the circulative transmission of TYLCV; its inhibition increases transmission. Hence, the efficiency of virus acquisition by whiteflies depends on the functionality of both plant chaperones and their cross-talk with other protein mechanisms controlling virus-induced aggregation.